Unraveling EFL Pre-Service Teachers’ TPACK through Self-Report Data - Yuni Dwi Susanti; Sri Wahyuni; Zulfa Sakhiyya (English Education Journal, 2023)
The technological revolution has changed the required knowledge and skills of teachers in facilitating the development of students’ 21st-century skills. In light of this, Technological Pedagogical Content Knowledge (TPACK) has been defined as a useful conceptual framework to help define the knowledge base needed for effective technology integration into classroom practices. However, generally, teacher professional education programs do not help teacher candidates develop TPACK. From this standpoint, the purpose of the study was to better understand the nature of pre-service English teachers’ TPACK over the professional development program named Pre-Service Teacher Professional Education (TPE) or Pendidikan Profesi Guru (PPG) Prajabatan. A survey was applied to examine 30 EFL pre-service teachers’ TPACK using self-report as the data source. The self-report was adopted from Schmid et al. (2020), and it consists of 28 items of the seven TPACK components. The results demonstrated that EFL pre-service teachers see the value of technology for teaching English. They highly perceived their TPACK competencies, especially for the TK construct (M=4.05) and the TPACK construct (M=4.08). They need more guidance on how to effectively integrate technology though. Thus, teacher professional education programs should redesign various methods of courses to provide more opportunities for pre-service English teachers to teach with technology since experiences had the most effect on beliefs.